Metabolic Glycoengineering Enables the Ultrastructural Visualization of Sialic Acids in the Glycocalyx of the Alveolar Epithelial Cell Line hAELVi - Brandt, Raphael; Timm, Sara; Gorenflos López, Jacob L.; Kwame Abledu, Jubilant; Kuebler, Wolfgang M.; Hackenberger, Christian P. R.; Ochs, Matthias; Lopez-Rodriguez, Elena (Frontiers in Bioengineering and Biotechnology, 2021)
The glycocalyx - a plethora of sugars forming a dense layer that covers the cell membrane – is commonly found on the epithelial surface of lumen forming tissue. New glycocalyx specific properties have been defined for various organs in the last decade. However, in the lung alveolar epithelium, its structure and functions remain almost completely unexplored. This is partly due to the lack of physiologically relevant, cost effective in vitro models. As the glycocalyx is an essential but neglected part of the alveolar epithelial barrier, understanding its properties holds the promise to enhance the pulmonary administration of drugs and delivery of nanoparticles. Here, using air-liquid-interface (ALI) cell culture, we focus on combining metabolic glycoengineering with glycan specific electron and confocal microscopy to visualize the glycocalyx of a recently immortalized human alveolar epithelial cell line (hAELVi). For this purpose, we applied different bioorthogonal labeling approaches to visualize sialic acid – an amino sugar that provides negative charge to the lung epithelial glycocalyx – using both fluorescence and gold-nanoparticle labeling. Further, we compared freeze-substitution and cytochemical electron microscopy embedding protocols for their capacity of contrasting the glycocalyx. In our study, we establish hAELVi cells as a convenient model for investigating human alveolar epithelial glycocalyx. Transmission electron microscopy revealed hAELVi cells to develop ultrastructural features reminiscent of alveolar epithelial type II cells (ATII). Further, we visualized extracellular uni- and multilamellar membranous structures in direct proximity to the glycocalyx at ultrastructural level, indicating putative interactions. The lamellar membranes were able to form structures of higher organization, and we report sialic acid to be present within those. In conclusion, combining metabolite specific glycoengineering with ultrastructural localization presents an innovative method with high potential to depict the molecular distribution of individual components of the alveolar epithelial glycocalyx and its interaction partners.